بناء مقياس الذكاء الأخلاقي وقف مستويات الحكم الأخلاقي للطلبة الجامعيين = Developing a measurement tool of moral intelligence for university students - Aljaj, Raja Muhammad Dib; Al-Hidabi, Dawood Abdulmalek Yahya; ALHammadi, Abdullah Othaman (University of Science and Technology, Sana'a-Yemen, 2018)
The study aims at developing a measurement tool of Moral Intelligence for university students based on Moral Judgment Levels. A Theoretical framework of Moral Intelligence based on Al-Ghazali philosophy of morals was developed. Then, a scale was designed and standardized. The study sample consist of 111 males and females biology student-teachers at the faculty of education, Sana’a University, Yemen.